Epipsammic diatoms in ağın region of keban dam lake in turkey - Caglar, M.; Selamoglu, Z.; Pala, G. (Green Wave Publishing of Canada, 2019)
In this study, the epipsammic diatoms in Ağın Region of Keban Dam Lake were analyzed at two stations between March-November 2016. As a result, 41 diatom taxa in total were recorded; while two of these taxa belonged to the Centrales, 39 of them belonged to the Pennales ordo. The epipsammic diatoms showed their best growth in early months of autumn and in summer when light and temperatures were high. During the study, at both of the stations, the most significant diatoms in terms of their numbers of individuals and frequency of occurrence were Navicula spp., Nitzschia spp. and Cymbella spp. © 2019, Green Wave Publishing of Canada. All rights reserved.
Keywords: Ağın; Epipsammic diatoms; Keban Dam Lake; Turkey